Colorful peacocks - Underwood, Deborah (Minneapolis, MN : Lerner Publications Co., 2007)
Describes the physical characteristics, life cycle, behaviors, and habitats of peafowl.
"Animals"--P. [4] of cover.
Includes bibliographical references (p. 31) and index.
Keywords: Peacocks